Balancing the active power of a railway traction power substation with an sp-RPC - Barros, Luis A. M. (2023)
The railway system is one of the safest, most efficient, and environmentally friendly means of land transport for people and goods. However, as the demand for mobility has increased, the current railway system has shown some weaknesses, requiring an increase in catenary power in order to be able to supply power to longer trains and faster locomotives, as well as to increase rail traffic. This paper proposes a control algorithm to be implemented in a sectioning post-Rail Power Conditioner (sp-RPC). The sp-RPC is connected to the neutral section between two traction power substations (TPS). With the control algorithm, it is possible to minimize the existing unbalance of the active powers of each TPS. In a regenerative braking condition, this surplus energy can be used to assist the traction of another locomotive on the existing overhead line. In this way, it is possible to increase the capacity of the overhead line. The analysis was performed with computer models using a modular multilevel converter (MMC) topology for the sp-RPC. Quantitative results for different consumption events of the locomotives and the analysis of the response to these variations are presented.